Functional Characterization of Cfap206 for Bivalve Ciliogenesis by RNAi and CRISPR/Cas9 Technologies - Wang, Yinghui; Zhu, Xiaomei; Lian, Shanshan; Li, Yiran; Hu, Naina; Hu, Xiaoli; Bao, Zhenmin; Wang, Shi (Frontiers in Marine Science, 2022)
Cilia are organelles located on the surface of eukaryotic cells and play important roles in numerous physiological and developmental processes. Cilia- and flagella-associated proteins (CFAP family) are well known due to their close relation to the assembly and functionalization of both cilia and flagella. In vertebrates, Cfap206 is reported to function during motile cilia assembly, and its abolished expression could lead to abnormal ciliary beating and decreased sperm motility. However, there is scarcely any information on the function of Cfap206 in marine invertebrates. Here, through using an ideal shellfish research model, the dwarf surf calm Mulinia lateralis, we explored the role of Cfap206 during embryonic ciliogenesis as well as during male gametogenesis. In trochophore larvae, effective knocking down or knocking out of Cfap206 was detected respectively through RNAi and CRISPR/Cas9 technology, showing an obviously decreased number of cilia. During the period of gonadal maturation, we managed to deliver the dsRNA of Cfap206 to male individuals for 14 days through carrier vector feeding. Significant suppression of Cfap206 was observed, together with impaired sperm motility and aberrant sperm tail assembly. The present study provided valuable information on gene function exploration methods in M. lateralis and further enriched the understanding of Cfap206 on ciliogenesis in marine invertebrates. Furthermore, by revealing the relationship between Cfap206 and spermatozoa flagellum, it is possible to generate male sterile populations in hermaphroditic marine organisms to improve crossbreeding efficiency.